صورة المرأة العاملة في يوتيوب عمل المرأة لأمجد النور (تحليل الخطاب النقدي): The Image of Working Women in Amjad Alnour’s YouTube Amal al-Mar’ah: a Critical Discourse Analysis - Farah, Zulfa Khuriyatul; Wahyudi, Jarot; Amin, Nurul (Jurusan Bahasa dan Sastra Arab Universitas Islam Negeri Alauddin Makassar, 2024)
صُوّرت المرأة كتابعة للرجل في سوق العمل في فيديو اليوتيوب عمل المرأة لأمجد النور. وكانت قضية المرأة العاملة في العالم العربي تشوق الباحثين إلى القيام بهذا البحث. فيهدف هذا البحث إلى تحليل صورة المرأة العاملة في فيديو عمل المرأة نقديا. وكان منهج البحث المستخدم في دراسة مكانة المرأة تحليل الخطاب النقدي لسارة ميلز حيث إنه حصل على بعض النتائج منها أن المرأة منذ القدم توضع في نفس المكانة إذ تعتبر أنها تابعة للرجل في سوق العمل. وخلال التطورات في أواخر هذا العقد، كانت المرأة في العالم العربي خاصة في قطر حصلت على مكانة أفضل مما كان في العصر الماضي. Abstract Women are depicted as subordinate to men in the workplace on the YouTube channel Amal al-Mar'ah. The topic of working women is an intriguing subject to explore in the Arab world. This research is aims to critically analyze the depiction of the position of working women in Amjad Alnour's YouTube Amal Al-marah. The methodology used to examine the position of women is Sara Mills' critical discourse analysis. The results of this study reveal that from the past until now, the position of women has remained the same, and they are considered subordinate to men in the world of work. The most recent development over the past decade is that women in the Arab world, particularly in Qatar, have attained a better status than in previous eras. Women can now pursue careers or work, provided that their guardians permit it.